Reformasi Sistem OSS dan Perizinan Berusaha Peraturan Pemerintah (PP) Nomor 28 Tahun 2025 tentang Penyelenggaraan Perizinan Berusaha Berbasis Risiko untuk Meningkatkan Invetasi Asing di Indonesia - Y, Yuliana (Media Hukum Indonesia (MHI), 2025)
This journal analyzes the fundamental reform brought by Government Regulation Number 28 of 2025 (GR 28/2025) to the Online Single Submission system (OSS) and Risk-Based Business Licensing (PBBR), and its impact on increasing Foreign Direct Investment (FDI) in Indonesia. This normative-doctrinal legal research analyzes the consistency and effectiveness of the new norms, supplemented by a socio-legal approach concerning the economic implications of investment policies. The findings indicate that GR 28/2025 codifies legal certainty guarantees through the establishment of strict Service Level Agreements (SLA) and the implementation of Positive Fictitious (FikPos) mechanisms in critical basic licensing stages (such as Marine Spatial Utilization Conformity Approval and High-Risk Permits), which significantly reduces the risks associated with time costs and bureaucratic coordination. Furthermore, the centralization of PB issuance authority for FDI to the Central OSS Institution (Article 138) functions as a legal shield to mitigate sub-national policy inconsistency. Although this reform is supported by a more flexible initial capital policy (Minister of Investment Regulation/BKPM 5/2025), the optimal success of increasing FDI depends critically on the speed of digital system synchronization and compliance with the implementation of national standards (NSPK) by Regional Governments, which must be accelerated within the 4-month transition period since the GR was enacted.